THE DILEMMA OF SHAREHOLDER CLAIMS FOR REFLECTIVE LOSS IN INTERNATIONAL INVESTMENT LAW: DIVERSIFICATION OR FRAGMENTATION? - Leila, Mohamed (AUC Knowledge Fountain, 2025)
Shareholder reflective loss (SRL) claims are filed by shareholders seeking compensation for the indirect damage they incur due to the injury directly suffered by their company. The loss of shareholders reflects the company’s loss in the form of a reduction of their share value. While national corporate laws generally adopt a consistent approach regarding SRL claims, fragmentation prevails on the international plane. Domestically, corporate laws prohibit SRL claims for policy reasons, granting the directly affected company the exclusive right of action. On the International level, customary international law, as deduced from the judgments of the International Court of Justice (ICJ), the European Court of Human Rights (ECtHR), and as codified in the International Law Commission (ILC) Draft Articles on Diplomatic Protection, aligns with domestic laws in rejecting SRL claims. Conversely, ISDS tribunals permit SRL claims, broadly interpreting investment treaties as granting shareholders direct access to ISDS for both direct and reflective loss claims. Using a comparative critical approach, this paper asserts that the ISDS standpoint is detrimental to corporations and the international law regime. The ISDS perspective distorts the fundamental principles of corporate laws. In particular, it disregards the corporate separate legal personality and its centralized management, ruining the corporate structure and governance. Further, this study argues that ISDS tribunals lack a unified, coherent SRL theory. Instead, the ISDS tribunals issue contradictory decisions with no clear rules regarding the extent of SRL claims, compromising the integrity and consistency of international investment law. To have a unified SRL claims approach on the international plane, this study concludes by proposing a defragmentation strategy based on the ILC report concerning the fragmentation of international law. Although it is a special international law regime, international investment law is not hermetically isolated from general international law. Hence, in light of the international law principles of “systemic integration” and “harmonization,” ISDS tribunals should reconsider their SRL approach, situating it within the broader context of general international law.